Peculiarities of water exchange of Quercus robur and Acer campestre in an oak-field maple forest - Bessonova, V. P.; Yakovlieva-Nosar, S. O. (Regulatory Mechanisms in Biosystems, 2024)
We studied the physiological and biochemical parameters of water exchange of two broadleaf forest species, Quercus robur L. and Acer campestre L., which grow under different levels of water supply. The study was conducted in the lower third of the northern slope and the middle third of the southern exposure slope in the “Viyskovyi” ravine. It was established that the content of total water in the leaves of Q. robur is higher than that of A. campestre under both mesophilic and xerophilic conditions. In A. campestre, the gradual dehydration of leaves during the growing season is more pronounced. The water-holding capacity of the leaves increases in both species, especially in July and August on the southern exposure slope, which is consistent with changes in the content of hydrophilic colloids. This can be considered as an adaptation of plants against rigorous hydrothermal conditions. The leaves of A. campestre retain water better and are characterized by a greater number of hydrophilic colloids compared to the leaves of Q. robur at different levels of water supply. Under xerophilic growth conditions, the suction power of the cellular junctions of leaves is more significant than under mesophilic conditions. At both experimental sites, this indicator is always higher in case of A. campestre, while the difference is greater only under xerophilic conditions. The increase in suction force in leaf cells occurs in parallel with the increase in soil dryness. The leaves of A. campestre have a greater water deficit and suction power, better water-holding capacity due to a greater content of hydrophilic colloids, and a lower intensity of transpiration. The leaves of Q. robur have a lower water deficit and a lower water-holding capacity, which is based on the ability to resist the lack of moisture by the development of a deep root system that allows water to be absorbed from its deep horizons. The obtained data make it possible to clarify the peculiarities of the water regime of tree species during their simultaneous growth in forest phytocoenoses and adaptation to different levels of soil moisture.